Cytotoxic Compound from Ethyl Acetate Fraction of Brucea javanica (L.) Merr Fruit Against HeLa Cell Line - Nurlina Nurlina; Ari Widiyantoro (UNIVERSITAS SEBELAS MARET (UNS), 2015)
The pure compound relatively (85 mg) was isolated from 4.5 kg Brucea javanica (L.) Merr. fruits sample. It was obtained from ethyl acetate fraction as a red-brownish amorphous solid of melting point 202-206 oC. Phytochemical screening of isolate showed positive result of terpenoid group. Based on analysis by UV, IR,1H-NMR and 13C-NMR spectroscopy and by comparison with known related compounds, indicated that isolate is quassinoid compound named Picras 3- en- 21- oat acid, 15-(acetyloxy)-13,20- epoxy-3-(ß-D- glucopyranosyloxy)-11, 12- dihydroxy -2, 16- dioxo -, methyl ester. Cytotoxic test using MTT assay method showed that compound have IC50 9,7 µg/mL.